Additive Manufacturing Conformity – A Practical View. (May 2022) - Tüzün, G.-J.; Roth, D.; Kreimeyer, M.
Abstract: With the dissemination of additive manufacturing (AM), numerous methods have emerged to support the design process. One possibility is to improve functional solutions through AM-conformal design. Literature-based criteria for the assessment of AM-conformity already exist. Within our study, we address the gap in criteria between a theoretical perspective and a practitioner's perspective. To this end, we first explain the application of the criteria through a use case and conduct an evaluation in an industrial environment adding practitioner's criteria to enable the assessment of AM-conformity.